MAKNA KONOTASI PADA TAKARIR INSTAGRAM KHOFIFAH INDAR PARAWANSA - Fadhilatun Nisa’; Ika Febriani (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2022)
The background of this research is the use of connotations on the Instagram captions of Khofifah Indar Parawansa, abbreviated as KIP, which is diverse and interesting. This study aims to describe the connotative meaning of KIP Instagram captions including (1) good connotative meaning and (2) bad connotative meaning. The method of this study is a qualitative by descriptive techniques. Reading techniques and documentation techniques is used to collect data. Meanwhile, to analyze data, it is used interactive data analysis techniques with the concept of Miles and Huberman. To check the validity of the data uses semantic validity. The results of this study show that there are two connotations, namely description of the meaning of good connotations and the meaning of bad connotations on KIP's Instagram captions. Good connotations include high connotations and friendly connotations, whereas bad connotations include hard connotations.